Technology and Business model for mechanized rice straw collection - CGIAR Research Program on Rice (2019)
The technology was transferred, demonstrated, and used for developing service provider business models in Vietnam, Cambodia and Philippines. About 6,000 straw balers are used in Vietnam in 2019 compared to several units in 2016. This intervention benefited to more than 300 extension workers and 3,000 farmers.